Punishment of international crimes in failed states: the Somali piracy imbroglio - Tsabora, James (Taylor & Francis (Routledge), 2014)
The legal impediments encountered in the global anti-piracy campaign off the coast of Somalia have awakened the international community to the realisation that there are still gaps in the international criminal justice system. One such gap relates to the non-existence of a readily available international criminal justice institution to address international crimes not covered by the Rome Statute of the International Criminal Court. The other gap is the lack of a legal mechanism to respond to international crimes arising from failed or collapsed states. This paper argues that international criminality from failed and collapsed states cannot be addressed by the mere prosecution of offenders in foreign courts; as long as the security vacuum exists in such states, it would be virtually impossible to combat international crimes originating from states in crisis. The actions taken by important international actors and organisations have been aimed at protecting the economic interests of the major powers of the North. These actions are essentially reactive, fragmented and not sufficiently holistic and are thus unlikely to succeed in providing a multifaceted approach needed in the fight against piracy.